Perancangan Sistem Pengaduan Bantuan Pada Korban Bencana Gempa Bumi menggunakan Metode Waterfall - Annisaa Utami (Jurnal Teknologi, 2021)
Earthquakes are the biggest threat of natural disasters in Indonesia because they occur suddenly and attack densely populated areas, such as large cities. Earthquakes with a magnitude of about 5 or 6 on the Richter scale occur in almost all regions in Indonesia. If the force of the earthquake passes 7 on the Richter scale, it can cause a lot of damage. After the earthquake caused many fatalities, material losses, and others arising from this disaster. During this time after an earthquake natural disaster, residents have difficulty informing victims and damage to homes because by using a system that is still manual. Website design using waterfall method, the website will make it easier for the public to report information related to the number of victims of each family member, damage to the house and disbursement of funds if the data has been approved by the officer.  The results of the study, namely getting information related to damage due to earthquake disasters from the side of residents / victims.